Hubungan antara Kecerdasan Emosional dengan Penyesuaian Diri Siswa Baru SMK - Ropiyah, Ropiyah; Awalya, Awalya (IAIN Kudus, 2021)
The Relationship between Emotional Intelligence and Vocational High School New Students Self Adjustment. This study aims to determine the relationship between emotional intelligence with the adjustment of new students of class X SMK Negeri 1 Bulakamba Brebes. The sample in the study was 78 students. This study uses a quantitative approach. The results of the data analysis showed that the level of emotional intelligence of new vocational high school students was in the medium category and the level of self adjustment was in the medium category. There is a positive and significant relationship between emotional intelligence and vocational high school new student self adjustment as indicated by the value (r) of 0.635 and a significance value of 0.000 < 0.05. While the coefficient of determination (r2) is 0.4032, this shows that emotional intelligence contributes 40% to the adjustment of new vocational high school students, so it be concluded that the higher level of emotional intelligence, the higher level of self adjustment.Keywords: Emotional Ntelligence, Self Adjustment, New Vocational High School Students